2022
DOI: 10.1186/s12876-022-02572-8
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal manometry for the diagnosis of pelvic floor disorders in patients with hypermobility spectrum disorders and hypermobile Ehlers-Danlos syndrome

Abstract: Introduction Functional gastrointestinal disorders (FGID) including impaired rectal evacuation are common in patients with Hypermobility Spectrum Disorder (HSD) or Hypermobile Ehlers-Danlos Syndrome (hEDS). The effect of connective tissue pathologies on pelvic floor function in HSD/hEDS remains unclear. We aimed to compare clinical characteristics and anorectal pressure profile in patients with HSD/hEDS to those of age and sex matched controls. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hypermobility spectrum disorders are characterized by joint hypermobility assessed using the Beighton score, coupled with one or more secondary musculoskeletal manifestations such as post-traumatic symptoms, pain, altered proprioception, and various features including pes planus, kyphosis, scoliosis, or joint misalignment (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Hypermobility spectrum disorders are characterized by joint hypermobility assessed using the Beighton score, coupled with one or more secondary musculoskeletal manifestations such as post-traumatic symptoms, pain, altered proprioception, and various features including pes planus, kyphosis, scoliosis, or joint misalignment (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Hypermobility spectrum disorders/hypermobile type Ehlers-Danlos Syndrome (HSD/hEDS) are connective tissue disorders that can affect multiple systems and result in a variety of symptoms including hyperextensible skin, frequent joint dislocations, orthostatic intolerance, autonomic dysfunction, functional gastrointestinal disorders, chronic pain, and fatigue. 1,2 In clinical practice, it is not uncommon to see patients severely affected by both migraine and HSD/hEDS, and the management can sometimes be challenging given the multitude of symptoms involved in this population. The recent study "Hypermobility Spectrum Disorders and Migraine in Adolescents-A Nationwide Study" conducted by Zloof et al 3 and published in Headache, is an important study that reported the association between (HSD/hEDS) and migraine in adolescents.…”
mentioning
confidence: 99%